Atributos físicos do solo em sistemas de culturas sob plantio direto na integração lavoura-pecuária - Lanzanova, Mastrângello Enivar (2005)
The integration between agriculture and cattle-raising has growing up in the last few years in Rio Grande do Sul state, Brazil. With the aim to evaluate the changes in some physical soil properties caused by different summer crop systems and pasture winter grazing frequencies, an experiment was carried out in Jari, central part of the state, in a Nitosol. The summer crop systems used, under no till, were: continuous soybean (MS), soybean-corn in crop rotation system (RS), continuous corn (MM), and corn-soybean crop rotation system (RM). The grazing frequencies used were: no graze (SP), graze at 28-day intervals (P28) and graze at 14-day intervals (P14). Winter pasture used was a mixture of black oat and ryegrass, under two nitrogen fertilization levels: 0 kg N ha-1 (0N) and 200 kg N ha-1 (200N). After two years of winter pasture utilization, soil water infiltration rate decreased significantly when the pasture were more frequently grazed (P14), compared with no grazed areas (SP), with values changing from 63 to 35 mm h-1. Soil bulk density, total porosity and microporosity showed low sensibility in detect soil compacted layers, caused by cattle trampling. Soil macroporosity, at 0-5 cm depth, had significant reduction, changing from 0,17 to 0,08 dm3 dm-3, in no grazed and graze at 14-day intervals areas, respectively. Soil penetration resistance observed after the grazing period, showed the compressive effect of cattle trampling, hitting values of 2,64 MPa in P14 and 2,67 MPa in P28, in the second year of the experiment. Aggregate geometric mean diameter was not affected by any used treatment. Except corn yield in P14, that had the smaller yield, yields at all were lower in P14 and P28, in comparison with SP. However no significant differences were observed. A tendency in highest yields was observed when crop rotations were used, even to corn or soybean. The results obtained showed that the integration between agriculture and cattle-raising is feasible, since the winter pasture management used be adequate, and the crop rotation be present. Key words: Integrated agriculture cattle-raising system, no tillage, cattle trampling, soil compaction, winter pasture.